The Efectiveness Of The Question And Answer Method Through A Humanistic Approach To Improve The Speaking Skill Of Grade 9 Students At MTS Muhammadiyah Swasta Lawang - Hanif Wazkia; Eka Rizal; Arman Husni; Oktarina Yusra (Innovative: Journal Of Social Science Research, 2023)
research was prepared by Hanif Wazkia,registration number: 2218047. Departement Arabic language education, college of education and educational sciences, syeikh Muhammad Djamil Djambek State Islamic University, Bukittinggi, with the topic: “ The Efectiveness Of The Question And Answer Method Through A Humanistic Approach To Improve The Speaking Skill Of Grade 9 Students At MTS Muhammadiyah Swasta Lawang”.Problems in education Language Arabic, the writer fids especially in speaking skills in the low participation of students in pronouncing vocabulary in the learning and teaching process, students afraid of making mistakes in speaking Arabic because they are not used to using it, some students do not like Arabic because it is difficult to learn. The teaching method used a teacher does not help students to improve reading skills. Therefore, the writer sees that the research question is to what extent the efectiveness of the question and answer method through a humanistic approach to improve the speaking skill of grade 9 students at MTS Muhammadiyah Swasta Lawang ? The type of research, writer used in this research is experimental research, experimental research this is an experimental approach based on determining all variable that effect the research problem except for one variable whose effect is being studied under these new conditions. And number of the research community is 90 students, and the researcher takes a sample in this thesis by the intentional method which is 60 students. Then the research tool: observation,interview, and test. The result of the research use of the method of question and answer method through a humanistic in MTS Muhammadiyah Swasta Lawang. This indicates a high post-test results in experimental class. There is a real difference in the result calculation T (6,20) that is greater than the result of the table T 4,755. The extent of the effectiveness of the interrogation method in the light of the human approach means 2,1.